Neuroanatomy of the European uppermost Cretaceous stem turtle Kallokibotion bajazidi. (April 2021) - Martín-Jiménez, Marcos; Codrea, Vlad; Pérez-García, Adán
Abstract: Kallokibotion bajazidi is one of the few stem turtles identified in the Upper Cretaceous of Europe. This form, exclusive to Maastrichtian outcrops of the Hațeg Basin (Romania), was described almost a century ago by the famous paleontologist Franz Nopcsa. However, it was identified as an enigmatic taxon until the end of the 20th century due to the limited available information. Recent studies have significantly improved knowledge about this taxon, confirming its attribution to a stem turtle, and being proposed as the sister taxon of the crown Testudines. The first three-dimensional reconstruction of the skull of this bizarre turtle is presented here. It has been made from the best-preserved skull so far known, the information provided by this specimen being complemented by that of an unpublished basicranium, which is analyzed in detail. This study allows to improve knowledge about the cranial osseous anatomy of the species, its phylogenetical identification as form closely related with the crown Testudines being supported. Furthermore, its neuronanatomical study is carried out. Detailed neuroanatomical analyzes on a very limited number of stem turtles have so far been performed. Considering the phylogenetic position of Kallokibotion bajazidi, the comparison of characters linked to the endocast, cranial nerves, nasal cavities, inner ears and circulatory system with those of these forms, as well as with those of members of the stem group, is carried out. Implications relative to the sensory capabilities interpreted for Kallokibotion bajazidi are discussed, the hitherto poorly supported hypothesis regarding its identification as a terrestrial turtle being supported. Highlights: The three-dimensional reconstruction of the skull of Kallokibotion bajazidi is done. It is based on the best-preserved skull and on an unpublished basicranium. New characters support its atribution to the sister taxon of the crown Testudines. Its neuronanatomy is analyzed and compared with those of basal and derived forms. Its sensory capabilities allow to support that it corresponded to a terrestrial form.